DETERMINAN KINERJA KEUANGAN PEMERINTAH DESA DI KECAMATAN RANTAU KABUPATEN ACEH TAMIANG - Nuriansyah Putra; Afrah Junita; Meutia, Tuti (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This study aims to analyze the influence of regulation, leadership, human resources (HR), and organizational culture on the financial performance of village governments in Rantau District, Aceh Tamiang Regency. The sample was selected using a purposive sampling method, with a total of 64 respondents. The data were analyzed using Partial Least Squares (PLS), including tests of the outer model, inner model, and hypothesis testing. The results indicate that: (1) regulation has a positive and significant effect on financial performance, (2) leadership has a positive and significant effect on financial performance, (3) human resources have a positive and significant effect on financial performance, and (4) organizational culture also has a positive and significant effect on financial performance. This study is limited by a relatively small sample size and a restricted research area, which may limit the generalizability of the findings. Future research is suggested to expand the study area, increase the number of respondents, and consider additional variables such as internal control systems or community participation in village financial management.